Two new species of the genus Leipsuropus (Crustacea: Amphipoda: Podoceridae) from Japanese and Korean waters - Ariyama, Hiroyuki (Zootaxa, 2012)
Two new species of the amphipod genus Leipsuropus Stebbing, 1899 are described. Leipsuropus astericolus sp. nov.was collected from the surface of a starfish in Japanese waters and L. hongi sp. nov. from the bottom in Korean waters.Both species have distinct projections on dorsal and lateral surfaces of head, pereonites 1–7 and pleonites 1, 2, and theprojections were acute in L. astericolus and blunt in L. hongi. These new species are quite different from L. parasiticus(Haswell, 1879) in Australian waters which has only dorsal rugae on pereonites 1–5. They are also distinguishable fromL. sinensis Ren, 2012 in Chinese waters in their sinuate palms of the male gnathopod 2. A key to species of the genus is provided.